A new pH/NIR responsive theranostic agent for magnetic resonance imaging guided synergistic therapy. Issue 12 (4th February 2021) - Du, Yechao; Wang, Daguang; Wang, Shuo; Li, Wei; Suo, Jian
Abstract : A new nanotheraontic agent for magnetic resonance imaging (MRI) guided combined photothermal therapy (PTT) and chemotherapy has been reported. Abstract : New nano-reagents with diagnostic imaging and therapeutic functions are very important for precision medicine against cancer. In this work, a new nanotheraontic agent for magnetic resonance imaging (MRI) guided combined photothermal therapy (PTT) and chemotherapy was constructed based on polydopamine (PDA) functionalized copper ferrite nanospheres (PDA@CFNs). The high relaxivity makes it possible for PDA@CFNs to become a promising MRI contrast agent, providing necessary and exhaustive information for tumor diagnosis. In addition, because both CFNs and PDA have strong near-infrared (NIR) absorption, PDA@CFNs exhibit excellent photothermal performance. Highly effective tumor ablation is achieved in a mouse model through PTT and pH/NIR triggered on-demand chemotherapy. These findings reveal that constructing smart pH/NIR responsive multifunctional theranostic agents is a feasible strategy for precision cancer therapy.